Efficacy of Ontario Rabies Vaccine Baits (ONRAB) against rabies infection in raccoons. Issue 32 (6th August 2018) - Gilbert, Amy; Johnson, Shylo; Walker, Nikki; Wickham, Chad; Beath, Alex; VerCauteren, Kurt
Highlights: Ontario Rabies Vaccine Baits protect raccoons against rabies virus infection. Greater vaccine immunogenicity was observed in juvenile raccoons. Equivalent vaccine efficacy was observed in juvenile and adult raccoons. Observed similar virus neutralizing and binding antibody kinetics post vaccination. Evidence of immune priming despite vaccine failure in five adult raccoons. Abstract: In the US, rabies lyssavirus (RABV) only circulates in wildlife species and the most significant reservoir from a public and animal health perspective is the raccoon ( Procyon lotor ). Management of wildlife rabies relies principally on oral rabies vaccination (ORV) strategies using vaccine-laden bait delivery to free-ranging target hosts, in order to reduce the susceptible population to prevent the spread of and eliminate RABV circulation. Our objective was to evaluate efficacy of the Ontario Rabies Vaccine Bait (ONRAB) against a lethal RABV challenge in captive raccoons. Sham or live vaccine baits were offered to 50 raccoons and efficacy was evaluated in 46, split into two trials of 17 and 29 raccoons. Raccoons were challenged with a lethal dose of RABV 180 days post-vaccination and observed for 90 days post-infection. Raccoon bait interactions were assigned increasing integer scores for approach, oral manipulation, puncture, and consumption behaviors. Higher bait interaction scores were observed in the fall compared to the spring trial, indicating that more raccoons consumed baits in the fall. Although animal age did not explain variation in bait interaction scores, the geometric mean rabies virus antibody titers among juvenile vaccinates were higher than adults at all pre-challenge time points. The prevented fraction associated with ONRAB delivery was 0.73 (8/11, 95% CI 0.39–0.94) in the spring trial and 0.91 (21/23, 95% CI 0.72–0.99) in the fall trial. All sham-vaccinated raccoons (12/12) succumbed to rabies infection, in contrast to 15% (5/34) mortality among vaccinated raccoons. Our results indicate a high efficacy of ONRAB bait vaccination in protecting adult and juvenile raccoons against RABV infection for a minimum of six months. These data complement experimental field trials that have also demonstrated the potential of ONRAB for the control and prevention of RABV circulation in free-ranging raccoon populations in the US.